Offspring performance and recruitment of the pioneer tree Acacia caven (Fabaceae) in a fragmented subtropical dry forest. (26th February 2015) - Ashworth, Lorena; Calviño, Ana; Martí, María Leticia; Aguilar, Ramiro
Abstract The process of habitat fragmentation results in the breaking apart of originally continuous habitats, causing multiple changes in biotic and abiotic interactions. Alterations in resource availability and in mutualistic and antagonistic plant–animal interactions may impact plant offspring quantity and quality. Currently, several old fragmented systems evidence a process of flora homogenization, where shade‐tolerant species are replaced by pioneer light‐demanding species. Notably, the relationship between quantity and quality parameters of plant offspring production and the successful recruitment of pioneer species in fragmented forests has been poorly explored. Here, we assess population size, sapling recruitment and offspring performance of one of the most widespread tree species of subtropical South America, the native pioneer Acacia caven (Fabaceae). Population size of adults and saplings increased from small to continuous forests, whereas the sapling recruitment per adult tree (sapling/adult ratio) showed no significant differences among forests of different size. Seedling performance was negatively related to forest area and population size, implying potential superior competitive ability of seedlings produced in smaller populations compared to larger ones. Our results show that A. caven is resilient to habitat fragmentation effects, which may be ascribed to a set of advantageous ecological traits such as outcrossing, massive flowering, generalist pollination, drought resistance, rapid growth and re‐sprouting. Thus, this pioneer tree benefits from the availability of vacant sites and resources released by declining plant populations of other species, eventually becoming the dominant species in fragmented habitats. Pioneer native plant species with ecological traits such as A. caven may represent the silent successful survivors and new colonizers of fragmented habitats, the ubiquitous landscapes of the future.